Co-processing of olive bagasse with crude rapeseed oil via pyrolysis - Uçar, Suat (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2017)
The co-pyrolysis of olive bagasse with crude rapeseed oil at different blend ratios was investigated at 500ºC in a fixed bed reactor. The effect of olive bagasse to crude rapeseed oil ratio on the product distributions and properties of the pyrolysis products were comparatively investigated. The addition of crude rapeseed oil into olive bagasse in the co-pyrolysis led to formation of upgraded biofuels in terms of liquid yields and properties. While the pyrolysis of olive bagasse produced a liquid yield of 52.5 wt %, the highest liquid yield of 73.5 wt % was obtained from the co-pyrolysis of olive bagasse with crude rapeseed oil at a blend ratio of 1:4. The bio-oil derived from olive bagasse contained 5% naphtha, 10% heavy naphtha, 30% gas oil, and 55% heavy gas oil. In the case of bio-oil obtained from the co-pyrolysis of olive bagasse with crude rapeseed oil at a blend ratio of 1:4, the light naphtha, heavy naphtha, and light gas oil content increased. This is an indication of the improved characteristics of the bio-oil obtained from the co-processing. The heating value of bio-oil from the pyrolysis of olive bagasse alone was 34.6 MJ kg-1 and the heating values of bio-oils obtained from the co-pyrolysis of olive bagasse with crude rapeseed oil ranged from 37.6 to 41.6 MJ kg-1. It was demonstrated that the co-processing of waste biomass with crude plant oil is a good alternative to improve bio-oil yields and properties